Comparison of posterior decompression techniques and conventional laminectomy for lumbar spinal stenosis - Zhang, Yong; Wei, Fei-Long; Liu, Zhi-Xin; Zhou, Cheng-Pei; Du, Ming-Rui; Quan, Jian; Wang, Yan-Peng (Frontiers in Surgery, 2022)
Objectives To compare the efficacy of posterior decompression techniques with conventional laminectomy for lumbar spinal stenosis. Methods The Embase, PubMed, and Cochrane Library databases were searched with no language limitations from inception to January 13, 2022. The main outcomes were functional disability, perceived recovery, leg and back pain, complications. A random effects model was used to pooled data. Risk ratio (RR), mean difference (MD) and 95% confidence interval (CI) were used to report results. The study protocol was published in PROSPERO (CRD42022302218). Results 14 trials including 1,106 participants were included in the final analysis. Bilateral laminotomy was significantly more efficacious in improve functionality than laminectomy [MD: −2.94; (95% CI, −4.12 to −1.76)]. Low incidence of iatrogenic instability due to bilateral laminectomy compared with laminectomy [RR: 0.11; (95% CI, 0.02 to 0.59)]. In addition, between those who received bilateral laminotomy and those undergoing laminectomy, the result showed significant difference regarding recovery [RR: 1.31; (95% CI, 1.03 to 1.67)]. Conclusions This study provides evidence that bilateral laminotomy has advantages in functional recovery, postoperative stability, and postoperative rehabilitation outcomes. Further research is needed to determine whether posterior techniques provide a safe and effective option for conventional laminectomy.